URGENCY ANALYSIS OF STUDENT WORKSHEET DEVELOPMENT CONTAINED 4C SKILLS IN BIOLOGY SUBJECT - Hanivah Hanivah; Rahmadhani Fitri; Prima Yarni Alfi (Universitas Negeri Padang, 2021)
The 2013 curriculum encourages students to have critical thinking, creative thinking, collaboration, and communication skills (4C). For this reason, teaching materials are needed in accordance with the demands of the 2013 Curriculum such as Student Worksheets (LKPD). The purpose of this study was to find data at the defining stage of the 4C-skilled LKPD. The data collection technique was observation, interviews and questionnaires to teachers and students of SMA 1 Kec. Gunuang Omeh. The results showed that the teaching materials available in SMA 1 Kec. Gunuang Omeh and has used the 2013 Curriculum, but the LKPD used is only made with the Subject Teacher Session. LKPD made by MGMP. From the results of the curriculum analysis, the school has implemented the 2013 curriculum, but in its implementation it has not been maximal in prioritizing student-centered learning processes. Based on interviews with teachers, it was found that the problem in the learning process was that teachers were not used to developing 4C skills in students. As many as 70% of teachers use printed book teaching materials in the learning process, 10% use LKPD that do not meet the 4C skill criteria. Based on the results of interviews by students that 93% of students strongly agree with the development of 4C skills-oriented LKPD. Therefore, the development of a 4C skill-oriented LKPD is needed.